CBD resistant Salmonella strains are susceptible to epsilon 34 phage tailspike protein - Ibrahim, Iddrisu; Ayariga, Joseph Atia; Xu, Junhuan; Adebanjo, Ayomide; Robertson, Boakai K.; Samuel-Foo, Michelle; Ajayi, Olufemi S. (Frontiers in Medicine, 2023)
The rise of antimicrobial resistance is a global public health crisis that threatens the effective control and prevention of infections. Due to the emergence of pandrug-resistant bacteria, most antibiotics have lost their efficacy. Meanwhile, the development of new antimicrobials has stagnated, which leads to the creation of new and unconventional treatments. Bacteriophages or their components are known to target bacterial cell walls, cell membranes, and lipopolysaccharides (LPS) and hydrolyze them. Bacteriophages being the natural predators of pathogenic bacteria, are inevitably categorized as “human friends”, thus fulfilling the adage that “the enemy of my enemy is my friend”. Leveraging on their lethal capabilities against pathogenic bacteria, researchers are searching for more ways to overcome the current antibiotic resistance challenge. Bacteriophages are considered to be one of the most effective alternative therapies for multidrug resistant bacteria. In this study, we expressed and purified epsilon 34 phage tailspike protein (E34 TSP) from the E34 TSP gene which was previously cloned into a pET30a-LIC vector, then assessed the ability of this bacteriophage protein in the killing of two CBD-resistant strains of Salmonella spp. We observed that the combined treatment of CBD-resistant strains of Salmonella with CBD and E34 TSP showed poor killing ability whereas the monotreatment with E34 TSP showed considerably higher killing efficiency.